2020
DOI: 10.1186/s13073-020-00755-0
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequence association analysis of blood proteins in a longitudinal wellness cohort

Abstract: Background: The human plasma proteome is important for many biological processes and targets for diagnostics and therapy. It is therefore of great interest to understand the interplay of genetic and environmental factors to determine the specific protein levels in individuals and to gain a deeper insight of the importance of genetic architecture related to the individual variability of plasma levels of proteins during adult life. Methods: We have combined whole-genome sequencing, multiplex plasma protein profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 42 publications
(77 reference statements)
10
44
0
Order By: Relevance
“…This agrees with the finding that signatures of circulating proteomes are highly individual specific 45 . In addition, we recently reported that the human blood level of many proteins during adult life is to a large extent affected by genetics, confirming the unique and stable individual patterns of the proteome profiles 46 . Among the most variable proteins we find human growth hormone 1 and 2 (GH1 and GH2) 29 , which may be depending on the large variation in expression levels between men and women with growth hormone levels reported to be sex, age, BMI and exercise dependent 47 .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This agrees with the finding that signatures of circulating proteomes are highly individual specific 45 . In addition, we recently reported that the human blood level of many proteins during adult life is to a large extent affected by genetics, confirming the unique and stable individual patterns of the proteome profiles 46 . Among the most variable proteins we find human growth hormone 1 and 2 (GH1 and GH2) 29 , which may be depending on the large variation in expression levels between men and women with growth hormone levels reported to be sex, age, BMI and exercise dependent 47 .…”
Section: Discussionsupporting
confidence: 62%
“…The liver marker GGT was identified in relation to inflammatory markers such as IL-6 and this is not unexpected since the liver plays a pivotal role in inflammation by draining circulating lipids (TG and free fatty acids), and triggering cytokines release, which in turn promote CRP hepatocyte production 53 . The strong relationship between CRP and IL-6 has been recently reported along with other cytokines 46 , and the integrated CRP-centric perspective may shed light on CRP roles in inflammatory-based disorders. This study also involves a very comprehensive longitudinal profiling of immune cell composition in healthy individuals 54 .…”
Section: Discussionmentioning
confidence: 84%
“…Consistent with previous studies [21][22][23][29][30][31][32] , we found that age and sex had a widespread effect on plasma protein levels, each explaining on average 2.8% of the total observed variability (Figure 1, Supplementary Table 1, Methods). Similar figures were observed for the subset of immune-related proteins, i.e.…”
Section: Variation Of Plasma Protein Levels In a Well-defined Healthysupporting
confidence: 91%
“…Of the 52 subjects, 51 (98%) completed the 3-month follow-up visit. The non-diabetes control group consisted of 94 participants that completed the second year in the longitudinal Swedish SciLifeLab SCAPIS Wellness Profiling (S3WP) program [ [9] , [10] , [11] ] and did not have diabetes as judged from repeated fasting glucose and HbA1c measurements as well as baseline OGTT. The control group were examined twice during the same time-period and at the same site as the diabetes subjects (2016–2018, Wallenberg Laboratory, Gothenburg), and the mean values from these examinations were used in the data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have conducted a large research program to analyze “wellness” in the general population involving the molecular phenotypes of a longitudinal cohort, the Swedish SciLifeLab SCAPIS Wellness Profiling (S3WP) program. This has led to several articles regarding “wellness”, including Zhong et al., [9] , Dodig-Crnkovic et al. [10] and Tebani et al.…”
Section: Introductionmentioning
confidence: 99%